The Analysis of Implementation of Stunting Prevention Program Case Study at the Air Beliti Community Health Center, Tuah Negeri District, Musi Rawas Regency, 2021 - Yuli Zulaikha; Yuanita Windusari; Haerawati Idris (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to determine the performance or success rate of stunting prevention program implementation related to the characteristics of the institution structure, network and communication, community culture, community needs, and external networks at the Air Beliti Community Health Center, Musi Rawas Regency. The method of this research is quantitative research. The research was conducted at the Air Beliti Community Health Center, Tuah Negri District, Musi Rawas Regency. It was carried out from March to May 2021. The number of samples of the stunting program working team at the Air Beliti Community Health Center was 43. The results of research on factors related to the success of the stunting program at the Air Beliti Community Health Center, Musi Rawas Regency, were the characteristic variables of the institution's structure, network and communication, and community needs. The factors that are not related to the success of the stunting program are organizational culture and external networks. The conclusion of the implementation of the stunting prevention program at the Air Beliti Community Health Center, Musi Rawas Regency in general, has been going well, with positive community responses. Stunting program implementation factors that can affect the success of the stunting program are the characteristics of the institution structure, network and communication, and community needs.